Snapshot: Ecuador in 1920 - Szente-Varga, Mónika (Acta Scientiarum Socialium, 2015)
Snapshot: Ecuador in 1920 The book El Ecuador en el centenario de la independencia de Guayaquil, 9 de octubre de 1920. 1820–1920 [Ecuador at the centenary of the independence of Guayaquil, 9th of October, 1920. 1820–1920] was published in a bilingual, Spanish–English edition in New York on the occasion that the harbour had been freed from Spanish colonial rule a hundred years before. The volume targeted the reading public of the United States, and more specifically, the business circles. First, it offered a short written account of the country, which was followed by more than 150 pages of photographs. Via the pictures, we might catch a glimpse of Ecuador in 1920. We can also observe the way the elite of Guayaquil presented its city and country, and, moreover, what they wanted us to see.
Keywords: modernization; Guayaquil; transportation; banking system; exportation